2012
DOI: 10.1038/jp.2011.175
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic indomethacin infusion increases fractional cerebral oxygen extraction in ELBW neonates

Abstract: Objective: Intraventricular hemorrhage (IVH) occurs in up to 25% of very low birth weight (VLBW) preterm neonates. Previous studies found that indomethacin administered in the first 6 h of life reduces the incidence of severe IVH in VLBW neonates and decreases cerebral blood flow, suggesting a decrease in cerebral oxygen delivery. Using near-infrared spectroscopy (NIRS), we monitored cerebral oxygenation before, during and after slow indomethacin infusion in extremely low birth weight (ELBW) neonates to determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 15 publications
0
8
0
Order By: Relevance
“…Fowlie et al [34, 104] conducted a meta-analysis on 19 trials of prophylactic indomethacin therapy and found that prophylactic indomethacin has short-term benefits including reduction in symptomatic PDA, the need for duct ligation, and severe IVH with no evidence of either benefit or harm on neurodevelopmental outcome. More recently, prophylactic indomethacin was shown to decrease cerebral perfusion which may be harmful to the developing brain [105] and was found to worsen the short-term respiratory outcomes in ELBW infants [106]. …”
Section: When To Treat?mentioning
confidence: 99%
“…Fowlie et al [34, 104] conducted a meta-analysis on 19 trials of prophylactic indomethacin therapy and found that prophylactic indomethacin has short-term benefits including reduction in symptomatic PDA, the need for duct ligation, and severe IVH with no evidence of either benefit or harm on neurodevelopmental outcome. More recently, prophylactic indomethacin was shown to decrease cerebral perfusion which may be harmful to the developing brain [105] and was found to worsen the short-term respiratory outcomes in ELBW infants [106]. …”
Section: When To Treat?mentioning
confidence: 99%
“…NIRS studies have shown that indomethacin can alter cerebral oxygenation such as the fractional tissue oxygen extraction, although the magnitude of the changes appears to depend on the infusion protocol (5,14,15). Interpreting cerebral oxygenation in terms of energy metabolism is difficult because cerebral blood oxygenation depends on the balance between oxygen delivery and consumption.…”
mentioning
confidence: 99%
“…Although that effect appears to be less pronounced when indomethacin is administered by slow infusion,35 a small positive effect on blood pressure was recently also seen in a study of early postnatal indomethacin given over 1–2 h to prevent intraventricular haemorrhage, presumably as a result of an increase in cerebrovascular resistance 36. Since we do not have any information about cardiac output or vascular resistance in our patients, we cannot be sure about the exact mechanism of our findings.…”
Section: Discussionmentioning
confidence: 70%